2021
DOI: 10.1093/trstmh/traa171
|View full text |Cite
|
Sign up to set email alerts
|

Modelling trachoma post-2020: opportunities for mitigating the impact of COVID-19 and accelerating progress towards elimination

Abstract: Background The COVID-19 pandemic has disrupted planned annual antibiotic mass drug administration (MDA) activities that have formed the cornerstone of the largely successful global efforts to eliminate trachoma as a public health problem. Methods Using a mathematical model we investigate the impact of interruption to MDA in trachoma-endemic settings. We evaluate potential measures to mitigate this impact and consider alternat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…18 Recent modeling has further suggested that continued use of an annual MDA treatment program is unlikely to push these persistently endemic districts to the elimination threshold by the year 2030. 19 In response, the global trachoma program has begun to consider increased programmatic flexibility in dealing with districts slow to reach elimination thresholds. An enhanced antibiotic treatment regimen characterized by more frequent rounds and/or targeted rounds to children along with a continued focus on F and E interventions is clearly warranted for persistent trachoma as observed in Amhara.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recent modeling has further suggested that continued use of an annual MDA treatment program is unlikely to push these persistently endemic districts to the elimination threshold by the year 2030. 19 In response, the global trachoma program has begun to consider increased programmatic flexibility in dealing with districts slow to reach elimination thresholds. An enhanced antibiotic treatment regimen characterized by more frequent rounds and/or targeted rounds to children along with a continued focus on F and E interventions is clearly warranted for persistent trachoma as observed in Amhara.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings demonstrate the potential repercussions of halting or delaying MDA in endemic areas due to funding issues, political unrest, and pandemics. Recent modeling studies have suggested that interruptions in MDA due to the Coronavirus Disease 2019 (COVID-19) pandemic may delay reaching elimination targets unless a catchup approach that includes increased frequency of azithromycin distribution is employed [ 18 , 41 ]. The results of this systematic review provide some empirical evidence that discontinuation of azithromycin MDA at higher trachoma prevalence levels will likely lead to increased prevalence of ocular chlamydia infection.…”
Section: Discussionmentioning
confidence: 99%
“…For communities that rely on preventive MDA, setbacks are likely to be greater for those infections with higher effective reproductive numbers and therefore higher growth rates. Expected resurgences in schistosomiasis ( Kura et al, 2021 ; Toor et al, 2020 ), soil-transmitted helminthiases ( Malizia et al, 2021 ) and trachoma ( Borlase et al, 2021 ) may mean that these conditions will likely not achieve EPHP status until after 2030, particularly in high-prevalence settings ( NTD Modelling Consortium, 2020 ). On the other hand, delays in achieving 2030 WHO NTD targets may not be as pronounced for lymphatic filariasis ( Prada et al, 2021 ) and onchocerciasis ( Hamley et al, 2021 ), which do not transmit as quickly and may be more responsive to early implementation of catch-up strategies such as biannual MDAs and/or expanded coverage.…”
Section: The Impact Of Covid-19 On Global Control Of Human Parasitic Infectionsmentioning
confidence: 99%